PENDAMPINGAN HAFALAN TEMATIK QS. AL-HUJURAT AYAT 11 SEBAGAI UPAYA PENECEGAHAN BULLYING PADA REMAJA - Jannah, Syarah Nur Athari; Zulfikar Hafizd, Jefik (LPPM UKRI, 2026)
Verbal bullying remains a significant issue among madrasah adolescents despite their religious educational environment, indicating insufficient internalization of Qur’anic ethical values in daily social behavior. This community service program aimed to prevent bullying through thematic memorization assistance of Surah Al-Hujurat verse 11 integrated into the Qur’anic tahfidz program at Madrasah Aliyah Miftahul Anwar, Garut. The implementation employed educational, da’wah-based, and participatory approaches through guided memorization, verse interpretation, tasmi’ activities, anti-bullying seminars, and parental reinforcement via women’s religious study groups. The results demonstrated improved understanding of Islamic social ethics, more respectful communication patterns among students, and increased collective awareness to reject bullying practices. The program confirms that thematic tahfidz integrated with contemporary social issues is effective in strengthening adolescent character education and enhancing collaboration between schools and families.